Factors affecting urban and rural tolerance towards conflict-prone endangered megafauna in Peninsular Malaysia - Ange S.L. Tan (Global Ecology and Conservation, 2020)
The long-term survival of conflict-prone megafauna such as tigers Panthera tigris and Asian elephants Elephas maximus requires people’s tolerance and willingness to coexist with them. Understanding people’s attitudes can help design conservation interventions that are more effective and supported by various stakeholders. We studied Malaysian citizens attitudes towards local megafauna and the influence of urbanization, conservation awareness, local context, taxonomic bias, and conflict severity on people’s attitudes and tolerance towards endangered megafauna. We conducted 733 interviews in three locations with different degrees of urbanization (capital city, small town, and rural area). Interviews in the city and small town were conducted in zoos and shopping malls to investigate the role of local context. Our respondents showed relatively good knowledge of local wildlife and wildlife conservation issues and thought that wildlife conservation was predominantly the government’s responsibility. People in all groups showed a taxonomic bias, expressing more tolerance towards less conflict-prone tapirs than towards potentially more dangerous elephants, and even less towards tigers. Urbanization and awareness had consistently positive effects on people’s attitudes, while the local context (zoos vs shopping malls) had very minor effects. Our results suggest that awareness campaigns can have a positive effect to promote positive attitudes towards wildlife in Malaysia and the need for stratified approaches when it comes to conservation campaigns. In urban settings, efforts should be made to enhance people’s sense of ownership and responsibility in conservation, while in rural areas efforts should focus on reducing the cost of conflict on people while promoting tolerance and willingness to coexist with conflict-prone megafauna.